Attitude and Volunteering Intention among Undergraduate Malaysian Students - Mohammed Ghamdhan, Abeer; Ali ElMetwally, Amani; SyukriYeoh Abdullah UKM, Mohd; Abu Bakar, Azizi; Abdul Elah Ali Sallam, Abdullah (International Journal of Psychosocial Rehabilitation, 2019)
The purpose of this research is to study the impact of attitude among undergraduate students in Malaysia on voluntary intention. There were 500 respondents randomly selected from Malaysia Perlis University, Malaysia, but only 432 questionnaires were received. To academics and organization practitioners the findings of this study have theoretical and practical consequences. The results showed that the attitude had a direct positive and significant effect on voluntary intent. It was suggested that future research should look into comparing the variables in volunteering behavior context and specialist volunteering context such as a big sporting events and disasters.